THE SEMIOTIC ANALYSIS OF MICHAEL JACKSON'S LEAVE ME ALONE, EARTH SONG, AND HEAL THE WORLD MUSIC VIDEOS - Maliza, Nurfia; Arfanti, Yulia (PHILOLOGY Journal of English Language and Literature, 2025)
This study examines the semiotic meanings in Michael Jackson’s music videos Leave Me Alone, Earth Song, and Heal the World using Ferdinand de Saussure’s theory of the signifier and the signified. Through a qualitative descriptive method, the research analyzes lyrics and visual elements to uncover symbolic messages related to media criticism, environmental issues, and global unity. The findings reveal that each video conveys powerful social and emotional narratives: Leave Me Alone critiques celebrity culture, Earth Song protests environmental destruction, and Heal the World promotes peace and compassion. These videos function as visual texts that reflect social realities and serve as tools for cultural communication.